Penerapan Sistem Informasi Manajemen Pendidikan dalam Pengelolaan Administrasi di SDN Kemakmuran 1 dan MTs Ma’arif NU 4 Songgom Brebes - Ikrimatul Aola; Pebru Alim Tufando; Nurfuadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the application of educational management information systems in administrative management at SDN Kemakmuran 1 and MTs Ma'arif NU 4 Songgom Brebes. The author uses field research where researchers go directly to the field to obtain research data. The approach used is a descriptive qualitative approach to describe the application of educational management information systems in administrative management at SDN Kemakmuran 1 and MTs Ma'arif NU 4 Songgom Brebes. Data collection methods used in this study are interviews, observations and documentation. Furthermore, the author analyzes the data using the Miles and Huberman model by reducing data, presenting data and verifying data. Then the data is tested for validity with data triangulation. The results of the study indicate that the application of educational management information systems in administrative management at SDN Kemakmuran 1 and MTs Ma'arif NU 4 Songgom still has several obstacles in its implementation but can be categorized as quite good. This is evidenced by the existence of several applications to help manage the administration of the two schools.